Inequalities in oral health: estimating the longitudinal economic burden of dental caries by deprivation status in six countries - Gerard Dunleavy; Neeladri Verma; Radha Raghupathy; Shivangi Jain; Joao Hofmeister; Rob Cook; Marko Vujicic; Moritz Kebschull; Iain Chapple; Nicola West; Nigel Pitts (BMC, 2024)
Abstract Background The recent World Health Organization (WHO) resolution on oral health urges pivoting to a preventive approach and integration of oral health into the non-communicable diseases agenda. This study aimed to: 1) explore the healthcare costs of managing dental caries between the ages of 12 and 65 years across socioeconomic groups in six countries (Brazil, France, Germany, Indonesia, Italy, UK), and 2) estimate the potential reduction in direct costs from non-targeted and targeted oral health-promoting interventions. Methods A cohort simulation model was developed to estimate the direct costs of dental caries over time for different socioeconomic groups. National-level DMFT (dentine threshold) data, the relative likelihood of receiving an intervention (such as a restorative procedure, tooth extraction and replacement), and clinically-guided assumptions were used to populate the model. A hypothetical group of upstream and downstream preventive interventions were applied either uniformly across all deprivation groups to reduce caries progression rates by 30% or in a levelled-up fashion with the greatest gains seen in the most deprived group. Results The population level direct costs of caries from 12 to 65 years of age varied between US10.2 billion in Italy to US$36.2 billion in Brazil. The highest per-person costs were in the UK at US$22,910 and the lowest in Indonesia at US$7,414. The per-person direct costs were highest in the most deprived group across Brazil, France, Italy and the UK. With the uniform application of preventive measures across all deprivation groups, the greatest reduction in per-person costs for caries management was seen in the most deprived group across all countries except Indonesia. With a levelling-up approach, cost reductions in the most deprived group ranged from US$3,948 in Indonesia to US$17,728 in the UK. Conclusion Our exploratory analysis shows the disproportionate economic burden of caries in the most deprived groups and highlights the significant opportunity to reduce direct costs via levelling-up preventive measures. The healthcare burden stems from a higher baseline caries experience and greater annual progression rates in the most deprived. Therefore, preventive measures should be start early, with a focus on lowering early childhood caries and continue through the life course.